Can and Should the EU's Eastern Partnership be Saved? - Thorvaldur Gylfason; Inmaculada Martínez-Zarzoso; Per Magnus Wijkman (Center for Economic Studies and ifo Institute (CESifo), 2014)
In a major setback for the EU, only two of four Eastern Partnership countries actually initialed Association Agreements at the Vilnius Summit in November 2013. This paper asks what went wrong and what can be done about it. Using a gravity model to estimate the effects of deep and shallow free trade agreements for the Eastern Partnership states with Russia and the EU, the paper shows that the Eastern Partnership countries, including Ukraine, by far the largest in the group, gain significantly from free trade agreements with the EU, but gain little if anything from free trade agreements with Russia.
Keywords: F14; F51; F53; 330; free trade agreements; Eastern Partnership; European Union